To solve the given system of equations we will use the substitution method.
Subtracting 2x from the first equation we get:
![\begin{gathered} 2x+y-2x=-3-2x, \\ y=-3-2x\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/elqopq8bj1fgqddwx2v8962iz4x0l41yk4.png)
Substituting the above equation in the second one we get:
![x^2+(-3-2x)^2=5.](https://img.qammunity.org/2023/formulas/mathematics/high-school/e9hk2id2xihoj735as2om9uwgz6811ozvl.png)
Simplifying the above equation we get:
![\begin{gathered} x^2+(-3)^2+2\cdot(-3)(-2x)+(-2x^2)=5, \\ x^2+9+12x+4x^2=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/m924vut2tyqqk6pqsc3mh0j4hn23b2i91m.png)
Adding like terms we get:
![5x^2+12x+9=5.](https://img.qammunity.org/2023/formulas/mathematics/high-school/27tzdjmlau0x9yedxlji60bwuvzhv11syw.png)
Subtracting 5 from the above equation we get:
![\begin{gathered} 5x^2+12x+9-5=5-5, \\ 5x^2+12x+4=0. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/b2qdynyernfod7u16w1yi5qw12u1r3lgxi.png)
Now, notice that:
![5x^2+12x+4=(5x+2)(x+2)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/high-school/po1x3so1zhuggyrokj30k3oviqyyu8jtzg.png)
Therefore:
![(5x+2)(x+2)=0.](https://img.qammunity.org/2023/formulas/mathematics/high-school/4yg2f4w9m1di91654umy6j0zz6nihdwipu.png)
Now, we know that:
![a\cdot b=0\text{ if and only if }a=0\text{ or }b=0.](https://img.qammunity.org/2023/formulas/mathematics/high-school/grdjf77yatu2qpx8tpe5rvujvteimheky4.png)
Therefore:
![(5x+2)(x+2)=0\text{ if and only if }5x+2=0\text{ or }x+2=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/pb6sjjv77t44ybh1f6xv6aipfl3vyoaumx.png)
Then:
![x=-(2)/(5)\text{ or }x=-2.](https://img.qammunity.org/2023/formulas/mathematics/high-school/uzf7swaetyrxi6zjyq0ogr2uxy9id03cky.png)
Finally, substituting the above result in y=-3-2x we get:
![\begin{gathered} y=-3-2(-(2)/(5))=-3+(4)/(5)=-(11)/(5) \\ or \\ y=-3-2(-2)=-3+4=1. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8ksens8q2e01tp9k28pp4hnw03lczxn8xl.png)
Therefore, the solutions of the given system of equations are:
![(-(2)/(5),-(11)/(5))\text{ and }(-2,1)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/high-school/k51wcpnup2ikjv4n8bupgm82wh5jom6bup.png)
Answer:
![(-(2)/(5),-(11)/(5))\text{ and }(-2,1)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/high-school/k51wcpnup2ikjv4n8bupgm82wh5jom6bup.png)